Role of V. Vernadsky in becoming and development of structure of agrarian science in Ukraine - Chernova, N. F. (History of science and technology, 2015)
The role of the famous scientist, organizer of science, academician V. Vernadsky in the organization of Agricultural Scientific Committee of Ukraine – the main focus agricultural research in the country is observed through historical research, historical and comparative, analytical and synthetic, bibliography, and using the methods and sources of personalization and archival analysis. Integrated use of different ways to search, analysis and synthesis provided an opportunity optimal use of archival sources, published documents and printed publications. Contribution of V. Vernadsky is pointed to the development of agricultural science for various power systems on Ukrainian territory in 1919-1920.